Pathways to Anxiety and Depression in Autistic Adolescents and Adults - Richdale, Amanda L.; Lawson, Lauren P.; Chalmers, Alexa; Uljarević, Mirko; Morris, Eric M. J.; Arnold, Samuel R. C.; Trollor, Julian N. (Depression and Anxiety, 2023)
Individuals diagnosed with autism spectrum disorder (autism) commonly experience co-occurring anxiety and depression, which are significantly associated. These mental health conditions are also variously associated with increased autistic traits, insomnia, intolerance of uncertainty (IU), sensory sensitivity, and autonomic symptoms. However, no research has explored the relationships between IU, sensory sensitivity, autonomic symptoms, insomnia, and autistic traits and how they might be associated with anxiety and depression in autism. This study took a transdiagnostic approach to explore the relationships between anxiety, depression, autistic traits, insomnia, IU, sensory sensitivities, and autonomic arousal in 222 autistic people aged 15-80 years (55.7% female) using path analysis. Four plausible, theoretical models were tested, with model 1 providing best fit and explaining 48% of variance in depression, 37% of variance in anxiety, and 29% of variance in insomnia. Autistic traits and IU were directly associated with anxiety and indirectly associated with depression through anxiety. Anxiety, insomnia, IU, and sensory sensitivity were all directly associated with depression; autonomic arousal and sensory sensitivity were also indirectly associated with depression through insomnia. Thus, multiple pathways can lead to anxiety and depression in autism, not only via known paths such as insomnia and IU but additionally via autonomic arousal and sensory sensitivities which are also elevated in autism. These findings suggest that careful clinical evaluation and individualised treatment plans are needed for autistic adults with anxiety or depression. When considering prevention, programs that help autistic adults reduce arousal, maintain good sleep, and reduce IU may prove fruitful.